A relevância do banco de atacado no mercado financeiro brasileiro - Longa, Barbara Rossini Costa (2023)
This research aimed to study the relevance of wholesale banks in the Brazilian financial market, examining the typical operations that are performed by them and their influence on the economic development of Brazil. To carry out this research, efforts were devoted to the search for different types of operations without the need to mention the names of the participants, given that the main objective was to explain the operations in question. For this, the volumes of operations carried out in 2022 by the 90 financial institutions participating in prudential conglomerates with segmentation S1, S2 and S3 were collected in the Brazilian Central Bank (Bacen) database, being classified as b1 (Commercial Bank, Multiple Bank with Commercial Portfolio or Caixa Econômica) and b2 (Multiple Bank without Commercial Portfolio or Investment Bank or Exchange Bank). It was also researched the operations that occurred in the Brazilian capital market from 2015 to 2022 as disclosed by the Brazilian Association of Financial and Capital Markets Entities (Anbima) and the main mergers and acquisitions that occurred and disclosed by the website Portal Fusões & Aquisições in 2022. Based on this research, it is evident the scope of the Brazilian financial market, the large volume of institutions authorized by the Central Bank to operate and the banks as one of the main intermediaries of the operations. This research also shows the large number of products in the financial market, from the simplest to the most complex, all aimed at meeting the most diverse needs of its customers